# Yahoo Web Search

1. ### Solve for U in this equation?

Multiply everything by ( u -1)( u -3) and then cancel identical terms to clear the fractions: ( u +7...3) / ( u -3) ( u +7)( u -3) + ( u -1)( u -3) = ( u +3)( u -1) Multiply everything out: u ^2 + 4u - 21 + u ^2 - 4u + 3 = u ^2 + 2u - 3 Combine terms: 2u^2 - 18...

4 Answers · Science & Mathematics · 09/05/2011

2. ### Let u = (1 1) and v = (1 2) and define U = span{ u } and V = span{v}.?

So, I presume, U + V simply means the union of the two sets, whereas U ...certainly U + V is not it. Why? Think about what U and V look like graphically. They are simply all multiples...

2 Answers · Science & Mathematics · 19/07/2011

3. ### Make u the subject of 1/ u - 1/v = 1/f?

1/ u - 1/v = 1/f Multiply throughout by u to get 1 - u /v = u /f Now multiply by v to get v - u ... with focusing a lens in physics 1/ u + 1/v = 1/f. EDIT If the original question ...

5 Answers · Science & Mathematics · 24/05/2009

4. ### finding the equation for the tangent line using derivatives if f( u ) = u ^5 + 1 and u = g(x) = (x)^1/2 at x=1?

f( u ) = u ^5 + 1; u = (x)^1/2 if x = 1 The slope of the line tangent to f( u ) = u ^5 + 1, is f ( u ). You can find for the value of u , given u = (x)^1/2 if x = 1 u = (1)^1/2 u = 1 Lets...

2 Answers · Science & Mathematics · 07/03/2011

5. ### find u .v given | u +v|=1 and | u -v|=5?

Are u , v variables of ordinary numbers? If so then Iu + vI = 1 mean wither u + v = 1 or u + v = -1 Iu - vI = 5 means either u - v = 5 or u - v = -5...

1 Answers · Science & Mathematics · 16/06/2008

6. ### Prove A ∩ (A U B) = A?

... this case you must show that: 1) Show that A ∩ (A U B) is contained in A 2) Then show that...

4 Answers · Science & Mathematics · 28/03/2008

7. ### ∫2x√(2x+1) dx = (2/15)(3x-1)(2x+1)^3/2 + c. Show this result using the substitution u =√(2x+1)?

u = sqrt(2x + 1) u ^2 = 2x + 1 u ^2 - 1 = 2x 2u * du = 2 * dx u * du = dx ( u ^2 - 1) * u * u * du => ( u ^2 - 1) * u ^2 * du => u ^4 * du - u ^2 * du Integrate: (1/5) * u ^5...

1 Answers · Science & Mathematics · 04/12/2011

8. ### Write as an algebraic expression of u ?

( u >0) csc [ sec ^ -1 ( u / 2 ) ] = csc [ cosec^ -1 { u /sqrt( u ^2 - 4)} ] by triangle rule, hypotenuse = u ,base =2,so,perpend.can be found out by pythagoras theroem). = u /sqrt( u ^2 - 4) . (ans.)

1 Answers · Science & Mathematics · 16/09/2011

9. ### Linear Algebra : Consider two non-zero perpendicular vectors u and v?

If u and v are perpendicular , there is no projection of v onto u , and reverse too .- So u .v= IuI IvI cos T , T=pi/2 , cos pi/2 =0 and u .v=0...

2 Answers · Science & Mathematics · 14/05/2013

10. ### Prove the Statement (A U (B n C) = (A U B)n(A U C) for sets A, B, C)?

A U (B ∩ C) = (A U B) ∩ (A U C... U C), and (A U B) ∩ (A U C) ⊂ A U (B ∩ C) A U (B...

2 Answers · Science & Mathematics · 09/10/2008